Natural Compounds in Plant-Based Food (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Culinary herbs and spices confer characteristic flavors or coloring to food. In this Special Issue of Foods, we aim to focus on culinary herbs and spices from a health perspective. Substances of plant origin are often regarded as harmless. The intention of this Special Issue is to provide a science-based view of the health impact of naturally occuring ingredients in plants with a particular focus on the health impact of plants used as culinary herbs and spices. In this context, different aspects will be addressed, including toxicological, analytical, and regulatory issues regarding naturally occurring ingredients in culinary herbs and spices as well as in products, such as essential oils and the food supplements based on them. For this purpose, some select examples of these compounds will be utilized to illustrate potential effects on human health, together with knowledge gaps related to hazard and exposure assessment. Moreover, safety issues related to products, such as essential oils or food supplements containing extracts of culinary herbs and spices that have become widely available to consumers through several distribution channels in the EU, will be covered.